Comparison of the efficacy and safety of low-dose calcineurin inhibitors plus sirolimus plus mycophenolic acid with the standard-dose calcineurin inhibitors plus mycophenolic acid regimen in patients who received kidney transplants - Li, Li; Wan, Jiao; Li, Yizhi; Fang, Jiali; Li, Guanghui; Ma, Junjie; Chen, Zheng (Frontiers in Pharmacology, 2025)
BackgroundSirolimus (SRL) has shown its anti-rejection and renoprotective efficacy in patients with kidney transplantation. However, more evidence is still needed. The current study aimed to evaluate the efficacy and safety of an SRL-containing regimen in patients who received kidney transplants.MethodsFifty patients with end-stage renal disease who received kidney transplants were enrolled and divided into the calcineurin inhibitors (CNI) + mycophenolic acid (MPA)+ glucocorticoid (N = 22) and CNI + MPA + SRL + glucocorticoid groups (N = 28) according to the actual regimen that they received. The minimal plasma concentration of tacrolimus and cyclosporin was maintained at 6–10 ng/mL and 150–250 ng/mL in the CNI + MPA + glucocorticoid group and 4–6 ng/mL and 75–125 ng/mL in the CNI + MPA + SRL + glucocorticoid group. The minimal plasma concentration of SRL was maintained at 5–8 ng/mL.ResultsThe Cr at month (M)6, M12, and uric acid at M3 were lower, while the eGFR at M12 was higher in the CNI + MPA + SRL + glucocorticoid group compared with the CNI + MPA + glucocorticoid group (all P < 0.05). The acute rejection rate showed a lower trend in the CNI + MPA + SRL + glucocorticoid group compared with the CNI + MPA + glucocorticoid group without statistical significance. The urine BK virus at M3, M6, M9, and M12 was lower in the CNI + MPA + SRL + glucocorticoid group compared with the CNI + MPA + glucocorticoid group (all P < 0.05). Incidence of most adverse events was similar between groups, except that BK virus was lower in the CNI + MPA + SRL + glucocorticoid group compared with the CNI + MPA + glucocorticoid group (0.0% vs. 36.4%, P < 0.01).ConclusionLow-dose CNI combined with SRL regimen as the initial anti-rejection regimen indicates a comparable anti-rejection and better renoprotective efficacy with a satisfying safety profile compared with the standard regimen.